Penerapan Pendekatan Culturally Responsif Teaching dalam Pembelajaran Berbasis Proyek untuk Meningkatkan Hasil Belajar Siswa - Cyntya, Giova Wahyu; Amirul , Bagus; Putra, Aji Setya Gaya (Cipta Media Harmoni, 2025)
Inclusive and contextual education plays a vital role in improving student learning outcomes. The Culturally Responsive Teaching (CRT) approach integrates culture into the learning process, while Project-Based Learning (PjBL) provides deep learning experiences through project-based activities. This study aims to examine the effectiveness of implementing CRT within PjBL in enhancing the learning outcomes of fifth-grade students at SDN Burengan 2 Kediri on the topic of Cultural Heritage. This research is a Classroom Action Research (CAR) that utilized learning outcome tests and observations as data collection instruments. The pre-cycle results showed an average score of 72.3 with a mastery level of 28%. After the implementation of CRT in PjBL in the first cycle, the average score increased to 79.1 with a mastery level of 61%, and in the second cycle, it rose to 89.6 with a mastery level of 89%. In addition to improving academic performance, students' active participation also increased, as seen in their engagement in discussions and group projects. The findings of this study indicate that the integration of CRT in PjBL is effective in enhancing student learning outcomes and engagement. Therefore, this approach is recommended as a learning strategy that supports cultural diversity and enriches the learning experience in an interactive and contextual manner.